Food allergens analysis instrumentation and methods - Nollet, Leo M. L., 1948-; Hengel, Arjon J. van (Taylor & Francis, 2011)
"Covering all of the major recognized food allergens in the US and EU, this comprehensive work begins with an introduction to the problem and prevalence of food allergens. It discusses health issues and the presence of allergens in various food products, examines methodologies for analysis and detection, and details specific methods for each food type. Maintaining a consistent structure and format throughout, each chapter describes the properties of the allergen, and demonstrates the appropriate sample extraction and clean-up, separation and analysis, and detection and quantification techniques"--Provided by publisher.